Analisis Strategi Brand Image Kedai Kopi “Lussid Coffee” Melalui Media Sosial Instagram - Ahmad Zaki; Zura Fajri Rahmadani; Roro Sekar Putri Yunita Prasetyo; Lulu Khusniyah; Retno Ngesti Rahayu (Jurnal Ilmu Komunikasi, 2025)
In the digital age, social media has become an effective tool for building brand image and reaching a wider audience. This study aims to analyze the brand image strategy implemented by the “Lussid Coffee” cafe through Instagram as a digital marketing tool. The method used in this study is qualitative evaluation. The results show that Lussid Coffee consistently utilizes Instagram through visual branding strategies, storytelling, and active interaction with followers. This strategy has successfully created a strong brand image as an aesthetic, friendly, and contemporary coffee shop. Lussid Coffee builds its branding through Instagram, with content ranging from Instagram feeds, Instagram stories, and reels